Corticosteroid treatment in pulmonary sarcoidosis: do serial lavage lymphocyte counts, serum angiotensin converting enzyme measurements, and gallium-67 scans help management?. Issue 12 (December 1986) - Turner-Warwick, M; McAllister, W; Lawrence, R; Britten, A; Haslam, P L
Abstract : Thirty two patients with persisting pulmonary sarcoidosis fulfilling defined criteria for treatment were managed according to a standard clinical protocol. In this an attempt was made to achieve and maintain maximal radiographic and physiological improvement with individually titrated doses of corticosteroids. Lavage cell counts, serum angiotensin converting enzyme (SACE) determinations, and gallium-67 scans were planned at standard intervals but were not used in management decisions. The study analysed serial measurements in relation to changes in the clinical measurements. Twelve patients' radiographs showed complete clearing, seven cleared partially, and 13 had partial clearing with evidence of fibrosis. There was no predictive value in the initial lavage lymphocyte counts or the SACE or gallium measurements. Notably, in seven patients, substantial radiographic improvement was observed when the initial lavage lymphocyte counts were normal. Higher initial lavage neutrophil counts (p less than 0.02), higher initial radiographic profusion scores (p less than 0.02), and lower vital capacity (p less than 0.01) and carbon monoxide transfer factor (p less than 0.05) were related to incomplete clearing. A repeat study of the patients when their radiograph had cleared maximally showed that the levels of lavage lymphocytes, SACE, and gallium tended to fall, but frequently remained raised even in the presence of a normal radiograph or vital capacity or both. On the other hand, however, most of the patients with a normal lavage lymphocyte count showed persisting abnormality of the radiograph, lung function measurements, SACE, and gallium scan (or of at least one of these indices). The interrelationships between changes in clinical indices (radiograph, vital capacity, and transfer factor) and in lavage lymphocyte counts, SACE, and gallium scans showed that concordance was fairly poor in each comparison; lavage lymphocytes showed a greater major discordance than did the other pairs of measurements. Symptom free patients with normal or stable radiographic appearances have been followed for many months and have shown no clinical deterioration despite abnormal lavage lymphocyte counts, SACE, and gallium scans. Radiographic relapse, within the criteria defined, was seen in only four patients during the study; this was reflected in the gallium counts in three and in SACE and lavage lymphocyte counts measurements in two. It is concluded that serial lavage lymphocyte counts, serum angiotensin converting enzyme measurements, and gallium-67 scans are not consistently more sensitive methods by which to monitor patients with sarcoidosis during treatment than are serial measurements of high quality radiographs and results of standard lung function tests.